Effects of Hypothetical Iranian Accession to WTO on Iran’s Flower Industry Development: Industry Opinions - Riasi, Arash; Aghdaie, Seyed Fathollah Amiri (Consilience, 2013)
This study intends to find the main effects of Iran’s accession to WTO on development of Iranian flower industry. In this hypothetical case study the effects of Iran’s accession to WTO on four different groups including flower producers, flower exporters, flower importers, and flower distributors have been evaluated. In order to test the hypotheses of the research; one-sample t-test was used. The results indicated that Iran’s accession to WTO would increase direct foreign investment, competitive strength of flower exporters, related job opportunities, number of modern greenhouses, foreign exchange earnings, area under flower cultivation, and number of international flower distributor companies in Iran’s flower industry. The results also showed that Iran’s accession to WTO would not increase the annual amount of flower imports to Iran and would not decrease the size of Iranian flowers domestic market and the price of flower production’s raw materials.